Comparing Surgical and Conservative Treatment on Achilles Tendon Rupture: A Comprehensive Meta-Analysis of RCTs - She, Guorong; Teng, Qiang; Li, Jieruo; Zheng, Xiaofei; Chen, Lin; Hou, Huige (Frontiers in Surgery, 2021)
Abstract Background The achilles tendon is the strongest tendon in human and frequently injured, mainly in young to middle age active population. Increasing incidence of Achilles tendon rupture (ATR) is still reported in several studies. Surgical repair and conservative treatment are two major management strategies widely adopted in ATR patients, but the consensus of the optimal treatment strategy is still debated. We aimed at thoroughly reviewing the ATR topic with additional assessments and performed a most comprehensive meta-analysis of randomized controlled trials (RCTs). Method We comprehensively searched the database of PubMed, Embase, Cochrane and ClinicalTrial.gov and retrieved all randomized controlled trials comparing surgical and conservative treatment on Achilles tendon rupture for further analysis. Two independent reviewers performed data extraction and random effect model was adopted when I2 > 50%, with data presentation of risk ratio, risk difference or mean difference and 95% confidence interval. Results A total of 13 randomized control trials were included in this meta-analysis. A significant difference was observed in re-rupture, complication rate, adhesion to the underlying tendon, sural nerve injury and superficial infection. A substantial reduction in re-rupture rate could be observed for surgical treatment while the complication rate was higher compared with conservative treatment. Conclusion Surgical treatment revealed significance in reducing the re-rupture rate but was associated with a higher complication rate, while conservative treatment showed similar outcomes with a lower complication rate. Collectively, we recommend conservative treatment if patients’ status and expectations are suitable, but the surgeon and physician’s discretion are also crucial in decision making. Keywords Achilles tendon rupture; Surgery; Conservative; Clinical outcome; Meta-analysis Level of evidence Level II, meta-analysis